Bank capital structure, macroprudential policy and economic growth - Alves, Maurício Barbosa (2018)
We study the long-run impact of the adoption of macroprudential tools. We derive a dynamic general equilibrium model featuring endogenous TFP change and allowing banks to choose their balance sheet structure endogenously. Banks choose vulnerable balance sheet structure depending on perceptions about fundamental risk. The design of prudential tools matters because it changes the riskiness of assets in a particular way, possibly increasing banking ability to fund projects. This introduces a novel channel to explain economic growth: risk mitigation.We then use the model to show numerically that there is a non-linear relationship between long-run growth and macroprudential policy intensity for several prudential rules considered in the related literature. We derive a welfare function and show that a welfare-maximizing regulator faces a growth-risk trade-off: welfare is maximized when growth is below its maximum value for each policy design we consider.